Interferon-alpha responsible EPN3 regulates hepatitis B virus replication - Li, Xueqian; Wang, Zhe; Zhou, Weiping; Fu, Xuanhe; Zhang, Yunpeng; Sun, Ye; Yang, Biao; Bai, Yuxin; Dai, Chunwei; Xu, Xiaolun; Cui, Fan; Zhao, Ying; et al. (Frontiers in Medicine, 2022)
Hepatitis B virus (HBV) infection remains a major health problem worldwide, and the current antiviral therapy, including nucleoside analogs, cannot achieve life-long cure, and clarification of antiviral host immunity is necessary for eradication. Here, we found that a clathrin-binding membrane protein epsin3 (EPN3) negatively regulates the expression of HBV RNA. EPN3 expression was induced by transfection of an HBV replicon plasmid, and reduced HBV-RNA level in hepatic cell lines and murine livers hydrodynamically injected with the HBV replicon plasmid. Viral RNA reduction by EPN3 was dependent on transcription, and independent from epsilon structure of viral RNA. Viral RNA reduction by overexpression of p53 or IFN-α treatment, was attenuated by knockdown of EPN3, suggesting its role downstream of IFN-α and p53. Taken together, this study demonstrates the anti-HBV role of EPN3. The mechanism how it decreases HBV transcription is discussed.